2013
DOI: 10.5713/ajas.2012.12417
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Reliable Reference Genes for Real-time qRT-PCR Analysis of Zi Geese (<italic>Anser anser domestica</italic>) Gene Expression

Abstract: Zi geese (Anser anser domestica) belong to the white geese and are excellent layers with a superior feed-to-egg conversion ratio. Quantitative gene expression analysis, such as Real-time qRT-PCR, will provide a good understanding of ovarian function during egg-laying and consequently improve egg production. However, we still don’t know what reference genes in geese, which show stable expression, should be used for such quantitative analysis. In order to reveal such reference genes, the stability of seven genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Differences in gene ranking were also observed between shell gland and spleen. Similar discrepancies have been observed in our previous study 45 and elsewhere with different species and treatments 48 , 57 , 69 . With different algorithms in different programmes, slight change of gene stability orders can be expected by the analyses using these programmes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Differences in gene ranking were also observed between shell gland and spleen. Similar discrepancies have been observed in our previous study 45 and elsewhere with different species and treatments 48 , 57 , 69 . With different algorithms in different programmes, slight change of gene stability orders can be expected by the analyses using these programmes.…”
Section: Discussionsupporting
confidence: 91%
“…In different vertebrate species, different reference genes under different treatments have been validated in the reproductive system. GAPDH and HPRT1 were ranked as the two most stable reference genes in the ovary of geese 57 . In bovines, the two most stable reference genes in the uterus were GAPDH and YWHAZ 58 .…”
Section: Discussionmentioning
confidence: 99%
“…g . [ 16 , 69 71 ]). Indeed, it has been shown that tissue/cell type can have a larger influence on RG stability than treatment regime [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zi goose has high egg production and strong freeze resistance, which is suitable for feeding in North‐east China (Ji et al, ). However, because the goose breeding season is seasonal, their laying period is short (Xu, Wu, & Xu, ).…”
Section: Introductionmentioning
confidence: 99%